Du Pont System Analysis: Kinerja Keuangan Perusahaan Sub-Sektor Telekomunikasi yang Terdaftar di BEI Periode 2020-2022 - Lia Uswatun Nuha; Sri Isnowati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Financial performance is an assessment of a company's finances to see the manager's ability to generate profits for shareholders. This research aims to analyze the financial performance of telecommunications sub-sector companies listed on the IDX for the 2020-2022 using Du Pont System Analysis. The method used in this research is descriptive analysis method. The type of data used is quantitative data with a numerical scale sourced from secondary data from the financial reports of PT XL Axiata Tbk, PT Smartfren Telecom Tbk, PT Indosat Tbk, and PT Telkom Indonesia Tbk. The research results show that PT XL Axiata Tbk and PT Smartfren Telecom Tbk are not good financial performance because Profit Margin on Sales and Total Assets Turnover are below industry standards. PT Indosat Tbk only in 2020 not good financial performance, whereas in 2021 and 2022 had good financial performance. PT Telkom Indonesia Tbk is good financial performance because Profit Margin on Sales is always above industry standards. Keywords : Du Pont System Analysis; Financial performance; Profitability Ratio; Activity Ratio; Financial Ratios.